Strengthening implementation of diet-related non-communicable disease prevention strategies in Fiji: a qualitative policy landscape analysis - Sarah Mounsey; Gade Waqa; Briar McKenzie; Erica Reeve; Jacqui Webster; Colin Bell; Anne Marie Thow (BMC, 2022)
Abstract Background Noncommunicable diseases (NCDs) are the leading cause of death globally, and the World Health Organization (WHO) has recommended a comprehensive policy package for their prevention and control. However, implementing robust, best-practice policies remains a global challenge. In Fiji, despite political commitment to reducing the health and economic costs of NCDs, prevalence of diabetes and cardiovascular disease remain the highest in the region. The objective of this study was to describe the political and policy context for preventing diet-related NCDs in Fiji and policy alignment with WHO recommendations and global targets. We used a case study methodology and conducted (1) semi-structured key informant interviews with stakeholders relevant to diet-related NCD policy in Fiji (n = 18), (2) documentary policy analysis using policy theoretical frameworks (n = 11), (3) documentary stakeholder analysis (n = 7), and (4) corporate political activity analysis of Fiji's food and beverage industry (n = 12). Data were sourced through publicly available documents on government websites, internet searches and via in-country colleagues and analysed thematically. Results Opportunities to strengthen and scale-up NCD policies in Fiji in line with WHO recommendations included (1) strengthening multisectoral policy engagement, (2) ensuring a nutrition- and health-in-all policy approach, (3) using a whole-of-society approach to tighten political action across sectors, and (4) identifying and countering food industry influence. Conclusion Diet-related NCD policy in Fiji will be strengthened with clearly defined partner roles, responsibilities and accountability mechanisms, clear budget allocation and strong institutional governance structures that can support and counter industry influence. Such initiatives will be needed to reduce the NCD burden in Fiji.